Thermal Investigation of Cylindrical Lithium-ion Batteries for Different Loading using Experimental and Numerical Techniques. Issue 12 (1st December 2022) - Kumar, Ravindra; Chavan, Sandip
Abstract : With growing concerns over climate change due to automotive emissions and fossil fuel depletion, electric vehicles (EVs) have gained more interest as a mode of transportation. Mostly, lithium-ion batteries are being used as an energy storage system in EVs. Temperature plays a major role in lithium-ion battery performance, degradation, and safety. Thermal investigation of cylindrical lithium-ion batteries of different chemistry and shape factors (18650 NMC and 21700 NCA) is conducted for different charging/discharging rates (0.5 C, 1 C, 1.5 C) and surrounding temperatures (26 °C and 45 °C) using numerical and experimental techniques. The numerical technique involves the determination of the surface temperature of the battery by solving the energy balance equation using a suitable numerical method. The numerical technique proposed in this study is validated using the experimental technique and can predict the temperature with at least 90% accuracy during the entire charging and discharging cycle from a lower to higher loading rate and different surrounding temperatures. The impact of different battery internal and external parameters on battery temperature is carried out using validated numerical technique. Thermal investigation conducted in this research can help in deciding the operating strategies of the battery management system and further in designing the proper thermal management system.